2016
DOI: 10.1155/2016/1245815
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of Vancomycin Therapeutic Goals in Critically Ill Patients: Early Individualization May Be Beneficial

Abstract: Objective. The aim of our study was to assess and validate the effectiveness of early dose adjustment of vancomycin based on first dose monitoring in achieving target recommended goal in critically ill patients. Methods. Twenty critically ill patients with sepsis received loading dose of 25 mg/kg of vancomycin and then were randomly assigned to 2 groups. Group 1 received maximum empirical doses of vancomycin of 15 mg/kg every 8 hrs. In group 2, the doses were individualized based on serum concentrations of van… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 30 publications
1
28
1
Order By: Relevance
“…This is likely only to be achieved with individualised vancomycin dosing algorithms, based on specific patient characteristics (i.e. creatinine clearance, weight, age) . In the intensive care setting, individualised dosing using Bayesian forecasting has been shown to improve attainment of target vancomycin concentrations when compared to standard empiric dosing in adults .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely only to be achieved with individualised vancomycin dosing algorithms, based on specific patient characteristics (i.e. creatinine clearance, weight, age) . In the intensive care setting, individualised dosing using Bayesian forecasting has been shown to improve attainment of target vancomycin concentrations when compared to standard empiric dosing in adults .…”
Section: Discussionmentioning
confidence: 99%
“…creatinine clearance, weight, age). 47,48 In the intensive care setting, individualised dosing using Bayesian forecasting has been shown to improve attainment of target vancomycin concentrations when compared to standard empiric dosing in adults. 49,50 In neonates in intensive care, better attainment of target vancomycin concentrations has been shown with individualisation of dosing using a pharmacokinetic model, compared with dosing following standard guidelines (63 vs 39%, P < .02).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the logistic challenges of such determination in clinical practice, it was demonstrated that such value could be obtained with trough serum levels of vancomycin between 10 and 20 mg/L . Larger concentrations were studied, but without evidence of better therapeutic outcomes …”
Section: Vancomycinmentioning
confidence: 99%
“…A clinical study conducted by Shahrami et al showed that, after 20 critically ill patients received an attack dose of 25 mg/kg vancomycin, the strategy that best guarantees AUC/MIC ≥400 and serum level ≥15 mg/L are individual doses based on serum vancomycin concentration.…”
Section: Vancomycinmentioning
confidence: 99%
See 1 more Smart Citation